The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jwas.12809
|View full text |Cite
|
Sign up to set email alerts
|

The status of Florida pompano, Trachinotus carolinus, as a commercially ready species for U.S. marine aquaculture

Abstract: Owing to their high value, in the 1950s researchers and commercial ventures began investigating the potential of Florida pompano, Trachinotus carolinus, for aquaculture; however, initial efforts did not result in commercialization. In the early 2000s, a renewed interest in pompano as a candidate for aquaculture occurred, and over the last two decades, protocols have been developed that have allowed commercialization of pompano aquaculture. Florida pompano broodstock can be readily conditioned to spawn (26-28 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 122 publications
(161 reference statements)
1
24
0
Order By: Relevance
“…Therefore, the evaluation of alternative feedstuffs and development of a sustainable feed (both nutritionally balanced and cost-effective) is a key factor for sustainable and economically viable Florida pompano aquaculture in the United States. There are different nutritional studies on this species 13 25 . However, to the best of our knowledge, there is no reported information on the substitution of FM by clam meal (CM) in the diet of this species and its effects on the growth, body composition, hepatic enzymes, gut microbiome, and the health of Florida pompano.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the evaluation of alternative feedstuffs and development of a sustainable feed (both nutritionally balanced and cost-effective) is a key factor for sustainable and economically viable Florida pompano aquaculture in the United States. There are different nutritional studies on this species 13 25 . However, to the best of our knowledge, there is no reported information on the substitution of FM by clam meal (CM) in the diet of this species and its effects on the growth, body composition, hepatic enzymes, gut microbiome, and the health of Florida pompano.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis of the results showed that as a breeding object T. falcatus was worse than other candidates studied (Thouard et al 1990). In particular, for example, T. carolinus has more than 40 years of successful research history and has long been considered a very promising species of cultivation (Weirich et al 2021). The original reasons for the introduction of this species into the aquaculture of Asia are unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…Third, although in need of refinement, hatchery methods for larval rearing and weaning have been established (Cassiano et al, 2011; Cavalin & Weirich, 2009; Fu et al, 2021; Hauville, 2014; Weirich et al, 2021). Fourth, pompanos school naturally (Schrandt & Powers, 2015) and, under appropriate densities, are highly adaptable to various culture environments, accept pelleted feed, convert feed efficiently to flesh, while maintaining high survival and uniform growth (Chavez et al, 2011; Riche, 2009; Weirich et al, 2021), reaching market size within 6–9 months, depending on species and marketplace (McMaster & Gopakumar, 2021). Fifth, all species can be reared in cages, tanks and ponds under varying salinities (McMaster & Gopakumar, 2021), and they are compliant under conditions of low oxygen when compared to other marine carnivores.…”
Section: Introductionmentioning
confidence: 99%
“…Second, pompano can be induced to spawn in captivity by photoperiod manipulation, and human chorionic gonadotropin or GnRHa injection (Chang, 1993; Gopakumar et al, 2012; Hoff et al, 1972; Ranjan et al, 2018; Weirich & Riley, 2007) which permits year‐round egg collection from these highly fecund (Gilbert & Parsons, 1986) species. Third, although in need of refinement, hatchery methods for larval rearing and weaning have been established (Cassiano et al, 2011; Cavalin & Weirich, 2009; Fu et al, 2021; Hauville, 2014; Weirich et al, 2021). Fourth, pompanos school naturally (Schrandt & Powers, 2015) and, under appropriate densities, are highly adaptable to various culture environments, accept pelleted feed, convert feed efficiently to flesh, while maintaining high survival and uniform growth (Chavez et al, 2011; Riche, 2009; Weirich et al, 2021), reaching market size within 6–9 months, depending on species and marketplace (McMaster & Gopakumar, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation